Tinnitus Treatment with Oxytocin: A Pilot Study - Azevedo, Andreia Aparecida; Figueiredo, Ricardo Rodrigues; Elgoyhen, Ana Belen; Langguth, Berthold; Penido, Norma De Oliveira; Schlee, Winfried (Frontiers in Neurology, 2017)
Introduction: Tinnitus is the perception of sound in the absence of an external stimulus. It is a frequent condition for which there is as yet no pharmacological treatment approved. Auditory and non-auditory pathways are involved in tinnitus’ pathophysiology. Oxytocin is a neurohormone and eventual neurotransmitter that plays a complex role in social cognition and behaviour. Objective: To evaluate the potential of oxytocin as a tinnitus treatment. Study design: Two studies were performed. Study 1 was a long-term open pilot study, while study 2 investigated short-term effects with a double-blinded placebo controlled cross-over study. Setting: Ambulatory ENT care. Subjects and Method: In study 1, 15 patients were investigated over a 10 weeks period in an open-pilot study. In study 2, 16 patients were included in a placebo-controlled cross-over trial to investigate short-term effects following a single dose. Results: For the long-term study (study 1), ANOVA revealed a significant decrease in tinnitus sensation, both for the Tinnitus Handicap Inventor (THI) and Clinical Global Impression (CGI). Also the short-term effects in study 2 revealed a significant reduction of tinnitus because of the oxytocin nasal spray as measured with the Visual Analog Scale (VAS) and the Clinical Global Impression Scale. Conclusion: These preliminary studies demonstrated that oxytocin may represent a helpful tool for treating tinnitus and further larger controlled studies are warranted.